Multiple disadvantage and major life events - Kikkawa, D (Department of Social Services, 2015)
This article examines the impact of experiencing multiple major life events on the social and emotional outcomes of Indigenous children.
Footprints in Time: The Longitudinal Study of Indigenous Children: Report from Wave 5
Keywords: Children -- Indigenous; Health -- Mental; Life Events -- Impact; Health and wellbeing; Disadvantage, adversity and resilience; Health; Children; Life Events; Mental; Indigenous; Impact; Dsiadvantage, adversity and resilience; Health and wellbeing; Adversity and resilience